The Characteristics and Main Controlling Factors of the Upper Paleozoic Sandstone Reservoirs in Dongpu Depression, Bohai Bay Basin - Yu, Jifeng; Zhao, Xiangguang; Peng, Jun; Yang, Ziqun; Zhang, Hongjun (Frontiers in Earth Science, 2022)
Based on the existing core and logging data, as well as previous research achievements, various experimental data were obtained by means of thin section, casting thin section, scanning electron microscopy, X-ray diffraction analyses, and cathodoluminescence. These data were used for the purposes of examining the features, diagenetic characteristics, and diagenetic evolution sequences of the Upper Paleozoic reservoirs of the Dongpu Depression, and analyzing the main controlling factors. The research results showed that the reservoir lithology was mainly subarkose, sublitharenite, feldspathic litharenite, and lithic arkose. The reservoir was generally characterized by ultra-low porosity and ultra-low permeability, with low porosity and low permeability in some areas. The pore types mainly include primary intergranular residual pores, dissolution pores, intercrystalline micropores, and microfractures. The pore throats are small and the throat channels are poorly sorted. The diagenetic processes mainly include compaction, pressure dissolution, cementation, metasomatism, and dissolution features of the research area. The diagenetic stages were determined to be mainly the middle diagenetic stages (Stage A and Stage B). The delta distributary channel and distributary bay of the Upper and Lower Shihezi Formation, along with the river channel sub-facies of the Shiqianfeng Formation, were considered to be the strata with good reservoir conditions. Moreover, the sand grains are dominated by medium-to-good sorting properties, sub-roundness and sub-angular, which provided a good spatial basis for the development of the primary pores. The calcite and kaolinite in the interstitial materials were corroded, which played a constructive role in the generation of the secondary pores. The results of the compaction, pressure dissolution, and cementation analyses indicate destructive diagenesis, which potentially reduced the porosity and permeability values. However, the dissolution, metasomatism, and chlorite lining cementation indicate improved diagenesis, which potentially increased the porosity and permeability values.